Risk factors of hypertension in elderly and late adult hypertensions’ patients - Heni Maryati; Supriliyah Praningsih; Fitri Firranda Nurmalisyah; Siswati; Madiha Mukhtar (UPPM STIKES Pemkab Jombang, 2025)
According to WHO data in 2024, about 1.28 billion adults worldwide have hypertension, with a slightly higher prevalence of men than women before the age of 50, and after the age of 50, the prevalence is almost the same. In Indonesia, the incidence of hypertension reaches 34.11% of the adult population. Risk factors for hypertension according to WHO include unhealthy lifestyles such as lack of physical activity, excessive salt consumption, alcohol and cigarette consumption, and obesity. In addition, genetic factors, age, and certain medical conditions such as kidney disease or diabetes also play an important role, so it needs to be detected early so that the incidence of hypertension can be suppressed and blood pressure controlled so that complications do not occur. The purpose of the study was to analyze the risk factors for hypertension in Puton Village, Diwek District, Jombang Regency. This study is a correlational study with a cross-sectional design using a purpusive sampling method. The research subjects were elderly people in Puton Village, Diwek District, Jombang Regency according to the research inclusion criteria in 2024, totaling 30 people. The instruments used were blood pressure measurements, data on gender, age, BMI, cholesterol levels, blood sugar levels, uric acid levels. Bivariate analysis using Chi Square statistical test. Results Most (53.3%) are classified as grade 1 hypertension, Almost. Chi Square test results Ha is rejected which means there is no relationship between age, gender, body mass index (BMI), cholesterol levels, blood sugar levels and uric acid levels on the incidence of hypertension. It is necessary to detect other factors that affect the incidence of hypertension such as stress levels, lifestyle and diet so that risk factors are detected so that the incidence of hypertension can be suppressed and morbidity and mortality due to complications of hypertension can be avoided